Association of MBL2 Exon 1 Polymorphisms With Multibacillary Leprosy - Tiyo, Bruna Tiaki; Vendramini, Evelyn Castillo Lima; de Souza, Victor Hugo; Colli, Cristiane Maria; Alves, Hugo Vicentin; Sell, Ana Maria; Zucoloto, Sylmara Bessani Paixão; Visentainer, Jeane Eliete Laguila (Frontiers in Immunology, 2020)
Mannose-binding lectin (MBL) is a serum protein of innate immunity, with a central role in the activation of the complement system through the lectin pathway. This protein is encoded by MBL2 gene, and single-nucleotide polymorphisms located at exon 1, such as rs5030737 C>T (D variant), rs1800450 G>A (B variant), and rs1800451 G>A (C variant), may change the MBL structure and the serum concentration. MBL2 polymorphisms have been associated with several infectious diseases, including leprosy. Host immune response has a major impact on the clinical manifestation of leprosy since only a few individuals infected with Mycobacterium leprae will develop the disease. Therefore, the aim of this study was to evaluate the influence of MBL2 exon 1 polymorphisms (rs5030737, rs1800450, and rs1800451) on the MBL levels and leprosy immunopathogenesis. This case–control study included 350 leprosy patients from Southern Brazil, with 279 classified as multibacillary (MB) and 71 as paucibacillary (PB). The control group consisted of 350 non-consanguineous individuals, who were not diagnosed with leprosy or other infectious and autoimmune diseases. Genotyping was performed by PCR–sequence specific primers, and the MBL serum concentrations were evaluated by ELISA. MBL2 exon 1 polymorphisms were analyzed individually and grouped as genotypes, considering “A” as the wild allele and “O” as the presence of at least one polymorphism (D, B, or C variants). Differences were not observed in the distribution of genotypic and allelic frequencies between leprosy per se patients and controls. However, in a haplotypic analysis, the TGG haplotype presented a risk for development of leprosy per se in women when compared to the wild haplotype (CGG) (OR = 2.69). Comparing patients with MB and PB, in a multivariate analysis, the B variant was associated with the susceptibility of developing the MB form of leprosy (OR = 2.55). Besides that, the CAG haplotype showed an increased susceptibility to develop MB leprosy in women compared to men. It was observed that the A/O genotype in women was associated with a susceptibility to leprosy development per se (OR = 1.66) and progression to MB leprosy (OR = 3.13). In addition, the MBL serum concentrations were in accordance with the genotyping analysis. In summary, our data suggest that MBL2 exon 1 polymorphisms are associated with an increased risk to leprosy development and progression.